Characteristics and trends of clinical trials funded by the National Institutes of Health between 2005 and 2015. (February 2018) - Gresham, Gillian K; Ehrhardt, Stephan; Meinert, Jill L; Appel, Lawrence J; Meinert, Curtis L
Background: The National Institutes of Health is one of the largest biomedical research agencies in the world. Clinical trials are an important component of National Institutes of Health research efforts. Given the recent updates in National Institutes of Health trial reporting requirements, more information regarding the current state of National Institutes of Health–funded clinical trials is warranted. The objective of this analysis was to describe characteristics and trends of clinical trials funded by the National Institutes of Health over time and by Institutes and Centers of the National Institutes of Health. Methods: Interventional studies funded by the National Institutes of Health and registered in ClinicalTrials.gov between 2005 and 2015 were included in the analysis. Trials were identified from the 27 March 2016 Clinical Trials Transformation Initiative Aggregate Analysis of ClinicalTrials.gov database. A descriptive analysis of trials by year and National Institutes of Health Institute/Center was performed. Results: There were 12, 987 National Institutes of Health–funded clinical trials registered between 2005 and 2015. There were 1, 580, 1, 116, and 930 trials registered in 2005, 2010, and 2015, respectively. The majority were early-development trials (phases 0, 1, or 2; 53%), randomized (61%), and single-center (63%). Trial demographics have remained unchanged over time. Median trial sample size was 64 (interquartile range 29–192) with 10% of trials enrolling ≥500 participants. Most trials were completed within 5 years of enrollment start (69%). Trial characteristics varied considerably across National Institutes of Health Institutes and Centers. Results were reported under the assumptions that most National Institutes of Health–funded trials are registered in ClinicalTrials.gov and that trials are being registered completely and accurately. Conclusion: In conclusion, there has been a decline in the number of trials being funded over time, explained in part by a relatively constant budget, increases in trial costs, or other factors that cannot be quantified. National Institutes of Health–funded trials are relatively small and tend to be single-centered. There are substantial differences in the number and types of trials done by Institutes and Centers within the National Institutes of Health.